2014
DOI: 10.1177/1938965514564214
|View full text |Cite
|
Sign up to set email alerts
|

Winners and Losers during the Great Recession

Abstract: One of the factors that separated winning hotels from losers in the recession was the hotels’ management of marketing expenses. By matching a group of 100 winners to 106 losers, based on high or low financial performance during the nadir of the recent recession, the study highlights the effects of marketing expenses as one primary driver of revenue and profit. The study compares the two groups’ revenue and profitability metrics to determine the two groups’ financial performance as the recession wore on. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…A handful of studies (e.g., Kim & Lee, 2020;Koh et al, 2009b) have identified insignificant correlations between marketing expenditure and firms' financial performance (e.g., Tobin's q and return on assets). However, in line with most of the hospitality marketing literature (e.g., Hua et al, 2020;Pansiri, 2008;Singh & Dev, 2015;Wu, 2004), we expect to observe a positive relationship between marketing activities and firm performance. Second, strategic alliances with business partners or suppliers enable hospitality organizations to acquire market-and product-related knowledge by creating strong inter-organizational and cooperative networks (Cho et al, 2019;Wilke et al, 2019).…”
Section: Promotion-related Antecedents Of Firm Performancesupporting
confidence: 77%
“…A handful of studies (e.g., Kim & Lee, 2020;Koh et al, 2009b) have identified insignificant correlations between marketing expenditure and firms' financial performance (e.g., Tobin's q and return on assets). However, in line with most of the hospitality marketing literature (e.g., Hua et al, 2020;Pansiri, 2008;Singh & Dev, 2015;Wu, 2004), we expect to observe a positive relationship between marketing activities and firm performance. Second, strategic alliances with business partners or suppliers enable hospitality organizations to acquire market-and product-related knowledge by creating strong inter-organizational and cooperative networks (Cho et al, 2019;Wilke et al, 2019).…”
Section: Promotion-related Antecedents Of Firm Performancesupporting
confidence: 77%
“…Previous tourism research has typically looked at the effects of a health or economic crisis, such as the 2003 SARS outbreak and the 2007-2008 recession. However, the majority of these studies have concentrated on the financial or operational consequences of the crisis at the business or market level (e.g., Chen et al, 2007;Zheng, 2014;Singh & Dev, 2015). Using stress process models as a foundation (Kahn, 1981;Pearlin et al, 1981), this study demonstrates a chain of adversity experienced by unemployed and furloughed tourism workers during the pandemic, demonstrating that coronavirus threats, financial impacts, resources impacts and social isolation have resulted in high depression, low personal control, and negative health and well-being outcomes for this group.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Furthermore, financial difficulties caused significant health and psychological problems for laid-off workers or those on long-term leave (Wanberg, 2012). Several studies have examined the impacts of various economic or health crises, such as Severe Acute Respiratory Syndrome (SARS) in 2003 or the recession in 2007-2008. Most of these studies focused on the financial or operational impacts of the crises (e.g., Chen, Jang & Kim, 2007;Zheng, 2014;Singh & Dev, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a previous study by Withane (1991) reports that acquiring a proven business format is the main motive for franchisees to select a franchise. In the USA, training support, reasonable independence and acquisition of an established brand name (Peterson and Dant, 1990), together with franchise fees, are shown to be impactful to financial performance (Singh and Dev, 2015), and are, therefore, found to be the main motives for franchisees in selecting a franchise.…”
Section: Literature Reviewmentioning
confidence: 99%